2010
DOI: 10.1016/j.jtcvs.2009.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Aging impairs the angiogenic response to ischemic injury and the activity of implanted cells: Combined consequences for cell therapy in older recipients

Abstract: The outcome of cell therapy in older recipients is determined by a combination of age effects on the donor cells and on the recipients' endogenous responses. Donor cell age and recipient age are equally important contributors to the outcome of cell therapy; thus, novel biointerventions will need to target both components of the process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 29 publications
5
73
0
Order By: Relevance
“…Whether the routine use of older donors with depressed ventricular function would yield the same results cannot be ascertained from the current study. Aging has been found to reduce the angiogenic response to ischemic injury in animal models 24 and result in greater ischemia reperfusion injury and apoptosis. 25,26 A loss of cardioprotection and a decreased response to ischemic precondition have also been noted with aging, 27,28 although this has not been consistent across all studies.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the routine use of older donors with depressed ventricular function would yield the same results cannot be ascertained from the current study. Aging has been found to reduce the angiogenic response to ischemic injury in animal models 24 and result in greater ischemia reperfusion injury and apoptosis. 25,26 A loss of cardioprotection and a decreased response to ischemic precondition have also been noted with aging, 27,28 although this has not been consistent across all studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, animals used in these studies are usually healthy and young, as opposed to patients with CLI. This is even more relevant because it has been shown that age impairs the angiogenic response (Zhuo et al, 2010).…”
Section: The Hindlimb Ischemia Modelmentioning
confidence: 99%
“…Furthermore, most patients who could benefit from such therapy are elderly patients with multiple medical comorbidities. Unfortunately a number of recent studies have documented that MSCs obtained from elderly donors, and those with diabetes, renal failure or severe ischemic heart disease, demonstrate significantly reduced capacity for proliferation, differentiation and neovascularization, with increased levels of apoptosis in vitro and in vivo [4]. Such impaired autologous cells from sick elderly patients could therefore limit their therapeutic potential.…”
mentioning
confidence: 99%
“…For instance, in their study, MSCs were harvested from the sternum of patients undergoing cardiac surgery. These cells, taken from elderly donors, were previously shown to have a significantly lower capacity for differentiation, angiogenesis, survival and even proliferation [4]. It is of interest to note that in the in vitro studies, human MSCs used were instead harvested from young healthy donors.…”
mentioning
confidence: 99%